IMPLEMENTASI PENDIDIKAN INKLUSIF DI SEKOLAH MENENGAH REGULER: STUDI KASUS SMA NEGERI 1 PETARUKAN KABUPATEN PEMALANG - Menuk Rahmawati; Basukiyatno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Inclusive education is an educational approach that guarantees the rights of all students, including those with special needs, to obtain equal educational services in regular schools. This study aims to describe the implementation of inclusive learning at SMA Negeri 1 Petarukan, Pemalang Regency. Using a qualitative approach with a case study method, data were collected through observations involving subject teachers, homeroom teachers, the Counseling Guidance team, and inclusion students. The results indicate that the school has adapted aspects of materials, methods, models, and learning media. Good practices found include material simplification, peer tutoring, use of visual media, and school collaboration with parents through continuous communication. However, the implementation of inclusive learning still faces challenges such as limited teacher time in preparing differentiated materials, a lack of learning media capable of accommodating diverse learning needs, and suboptimal implementation of differentiated instruction. This study provides important implications for strengthening inclusive learning practices in regular secondary schools